The Price of the Calling: Exploring Clergy Compensation Using Current Population Survey Data - Schleifer, Cyrus (Journal for the scientific study of religion, 2016)
Previous research shows that clergy make less money than others with similar levels of education. We use Current Population Survey data to offer five contributions to knowledge about clergy compensation....